Roux-en-Y Duodenojejunostomy as Surgical Treatment for Congenital Duodenal Obstruction: A Case Report - Yani, Ahmad; Ruhimat, Albireza (The New Ropanasuri Journal of Surgery, 2026)
Introduction. Congenital duodenal obstruction is an anatomical abnormality in newborns. Various intrinsic and extrinsic etiologies can cause duodenal obstruction. The surgical treatment that is commonly performed on duodenal obstruction in neonates is duodenoduodenostomy. However, several etiological conditions, such as preduodenal portal vein (PDPV) and pancreatic annulare cause duodenoduodenostomy nearly impossible to perform, so an alternative surgery procedure with a good outcome is necessary. Case Illustration. A female neonate had been suspected congenital duodenal obstruction since pregnancy due to polyhydramnios. An OGT was inserted with greenish yellow residue after the baby was born. Based on abdominal x-ray examination, a double bubble appearance was seen. The patient then underwent surgery at 5 days old. Intraoperatively, there was a PDPV and annular pancreas covering the 2nd and 3rd part of the duodenum, so it was decided to perform Roux-en-Y duodenojejunostomy. Conclusion. In patients with congenital duodenal obstruction with special etiology and anatomy, such as PDPV and pancreatic annulare, it is possible to perform a Roux-en-Y duodenojejunostomy. Even though this operation is rarely performed on neonates and is more common in adult patients, it can be an alternative in cases of congenital duodenal obstruction.